A digital light processing 3D printed magnetic bioreactor system using silk magnetic bioink. (13th May 2021) - Ajiteru, Olatunji; Choi, Kyu Young; Lim, Tae Hyeon; Kim, Do Yeon; Hong, Heesun; Lee, Young Jin; Lee, Ji Seung; Lee, Hanna; Suh, Ye Ji; Sultan, Md Tipu; Lee, Ok Joo; Kim, Soon Hee; et al.
Abstract: Among various bioreactors used in the field of tissue engineering and regenerative medicine, a magnetic bioreactor is more capable of providing steady force to the cells while avoiding direct manipulation of the materials. However, most of them are complex and difficult to fabricate, with drawbacks in terms of consistency and biocompatibility. In this study, a magnetic bioreactor system and a magnetic hydrogel were manufactured by single-stage three-dimensional (3D) printing with digital light processing (DLP) technique for differentiation of myoblast cells. The hydrogel was composed of a magnetic part containing iron oxide and glycidyl-methacrylated silk fibroin, and a cellular part printed by adding mouse myoblast cell (C2C12) to gelatin glycidyl methacrylate, that was placed in the magnetic bioreactor system to stimulate the cells in the hydrogel. The composite hydrogel was steadily printed by a one-stage layering technique using a DLP printer. The magnetic bioreactor offered mechanical stretching of the cells in the hydrogel in 3D ways, so that the cellular differentiation could be executed in three dimensions just like the human environment. Cell viability, as well as gene expression using quantitative reverse transcription-polymerase chain reaction, were assessed after magneto-mechanical stimulation of the myoblast cell-embedded hydrogel in the magnetic bioreactor system. Comparison with the control group revealed that the magnetic bioreactor system accelerated differentiation of mouse myoblast cells in the hydrogel and increased myotube diameter and length in vitro . The DLP-printed magnetic bioreactor and the hydrogel were simply manufactured and easy-to-use, providing an efficient environment for applying noninvasive mechanical force via FDA-approved silk fibroin and iron oxide biocomposite hydrogel, to stimulate cells without any evidence of cytotoxicity, demonstrating the potential for application in muscle tissue engineering.